If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3=y-85/3
We move all terms to the left:
3-(y-85/3)=0
We add all the numbers together, and all the variables
-(+y-85/3)+3=0
We get rid of parentheses
-y+3+85/3=0
We multiply all the terms by the denominator
-y*3+85+3*3=0
We add all the numbers together, and all the variables
-y*3+94=0
Wy multiply elements
-3y+94=0
We move all terms containing y to the left, all other terms to the right
-3y=-94
y=-94/-3
y=31+1/3
| 3/4=-6e-5/8 | | -7+9k=-106 | | 3x^2+3x=97 | | 3/10(12x-16)=2/5(12-3x) | | -5+6r=-95 | | -1+5y+1=0 | | x^2+16x+81=0 | | 3=y−85/3 | | 1+5y+1=0 | | -49+4g=35 | | 9(r+3)=99 | | X^2+-8x+0=0 | | 3x-2=-7+9 | | 6w=45-3w | | 53+90+(2x+3)=180 | | 3t-2+t-5=-1 | | x^2=7x=1 | | 56+w=8w | | x^2+x+81=0 | | 2*x+5=x | | (x^2)-3.5x+39=0 | | (x^2)-3.5+39=0 | | -z+27=14 | | 7t-3=6(t+2) | | G=M2c2 | | 2+4y+5=0 | | 0=-16x+64x+80 | | t/13/4=41/2 | | 5.5x+3.4x=-11.04+4.1x | | x^2=3.5x-39 | | E=M2D56f | | 12x+10=65 |